KARAKTERISASI PERMEN JELLY UMBI BIT MERAH (Beta Vulgaris .L) DENGAN PENAMBAHAN EKSTRAK BUAH SIRSAK DAN VARIASI PEKTIN - Meilianti, Meilianti (Jurnal Distilasi, 2018)
Jelly candy is a kind of candy that liked from all society, specially from kids and teenagers. But now most of jelly candy is made from synthetic dyes and didn’t have any nutrients on it. Most of jelly candy is made of synthetic sweetener and also using chemical essence for its taste. It was the reason that pushed the development of using natural dyes in candy production. Jelly candy production that used beetroot potentially gives an attractive red color and add the nutritions on jelly candy. The production of jelly candy divide to 2 sample, the A sample is using 60% beetroot extract and 40% soursop extract. And B sample is using 70% beetroot extract and 30% soursop extract. This research using pectin variation, the variation is 1% ; 1.5% ; 2% ; 2.5%; and 3%. The analization of jelly candy product are moisture content, ash content, reducing sugar content and heavy metal (Pb) content. The best concentration in this jelly candy is on the A3 sample, because the sample fullfil all the test standar.